2017
DOI: 10.3390/geriatrics2020018
|View full text |Cite
|
Sign up to set email alerts
|

Stroke in Older Survivors of Ischemic Stroke: Standard Care or Something Different?

Abstract: Stroke is one of the leading causes of death and disability and it is more likely to occur in those who are older. Because people are living longer, the definition of "old" continues to evolve. Age alone should not influence the healthcare that a patient receives, however, evidence indicates that this does occur, especially in older patients. On the basis of the available evidence, it is time to reconsider whether or not stroke care should differ in older survivors of stroke and if so, why. This is a narrative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 82 publications
1
4
0
Order By: Relevance
“…Our sample's profile was similar to that of recent research ( 60 , 61 ). When assessing the relationship between functionality and QoL with the sociodemographic data, comorbidities, and risk factors presented by the stroke patients, we found that older and less educated patients showed less favorable participation in daily-life activities up to 2 years post-stroke ( 62 ).…”
Section: Discussionsupporting
confidence: 84%
“…Our sample's profile was similar to that of recent research ( 60 , 61 ). When assessing the relationship between functionality and QoL with the sociodemographic data, comorbidities, and risk factors presented by the stroke patients, we found that older and less educated patients showed less favorable participation in daily-life activities up to 2 years post-stroke ( 62 ).…”
Section: Discussionsupporting
confidence: 84%
“…Strategies need to be inducted in order to encounter this challenge [17]. Poor and unspecialized management of elderly patients suffering from stroke might even lead to higher financial and healthcare burden in the form of increased morbidity, long term disability, and placement in residential care [18]. Goldberg et al found in a collective of poor grade patients that unfavourable outcomes 6 to 12 months after aneurysmal SAH were strongly related to older age.…”
Section: Late Improvement Is Independent From Age and Wfns Gradementioning
confidence: 99%
“…[21][22][23] Advanced age is one of the most common reasons of withholding IVT. 24 Several previous relevant studies have shown that older patients (>80 years) generally have poorer outcome and higher rates of mortality regardless of receiving IVT, yet IVT can improve the final outcome in both groups of patients under and over 80 years. 4,21,25 TA B L E 1 Demographic and clinical characteristics and laboratory findings of patients ≥80 years old with poorer outcome or significant increased rates of sICH and mortality.…”
Section: Discussionmentioning
confidence: 97%
“…Advanced age is one of the most common reasons of withholding IVT 24 . Several previous relevant studies have shown that older patients (>80 years) generally have poorer outcome and higher rates of mortality regardless of receiving IVT, yet IVT can improve the final outcome in both groups of patients under and over 80 years 4,21,25 .…”
Section: Discussionmentioning
confidence: 99%